Temperatura S.A - Valdez Flórez, Enrique (1992)
Case study on a company that, due to little interest in the proper use of the computer system, makes a serious mistake that causes serious damage to one of its main customers. The objective is to motivate students in the matter of how difficult it is to understand the technology that others master, which often puts the manager at a disadvantage compared to others and arouses in him mistrust or suspicion towards his subordinates. Students will surely find that the central problem lies in the lack of adequate planning, which should not be rejected as bad. However, the teacher, with appropriate questions, should ensure that students realize the permanent danger of being technological outdated or having contempt for unknown technology. And he should encourage in them a willingness to be more cautious when they perceive information they do not understand and to take advantage of opportunities that significantly benefit those who seize them.